In-group Bias and the Police: Evidence from Award Nominations - Ba, Bocar A. (2019)
This paper examines the impact of in-group bias on the internal dynamics of a police department. Prior studies have documented racial bias in policing, but little is known about bias against officers due to lack of available data. We construct a novel panel dataset of Chicago Police Department officers, with detailed information on officer characteristics and work productivity. Exploiting quasi-random variation in supervisor assignment, we find that white supervisors are less likely to nominate black officers than white or Hispanic officers. We find weaker evidence that male supervisors are less likely to nominate female officers than male officers. We explore several theories of discrimination that can explain our main findings. Requiring interaction between supervisors and officers reduces the minority nomination gap, but white supervisors still exhibit in-group favoritism. Our findings suggest departments should focus on policies that address in-group bias due to its effect on career advancement